Impact of non-surgical periodontal therapy on systemic inflammatory biomarkers in patients with metabolic syndrome: A randomized controlled trial - Ravindranath Dhulipalla (Bioinformation, 2026)
Metabolic syndrome is associated with chronic low-grade inflammation and periodontal inflammation may add to this systemic inflammatory burden. Therefore, it is of interest to evaluate the effect of non-surgical periodontal therapy on periodontal parameters and systemic biomarkers among 80 patients with metabolic syndrome and Stage II/III periodontitis allocated to immediate therapy or delayed therapy control. At 3 months, the therapy group showed significantly greater reductions in probing pocket depth, clinical attachment loss, periodontal inflamed surface area, high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor-alpha and HbA1c than the control group. High-sensitivity C-reactive protein decreased from 4.8 ą 1.9 to 3.1 ą 1.4 mg/L in the therapy group compared with 4.7 ą 1.8 to 4.4 ą 1.7 mg/L in controls (between-group p